Familial Migraine with Vertigo and Tremor - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A family with dominantly inherited migraine headaches, episodic vertigo, and essential tremor is reported from the UCLA School of Medicine, Los Angeles, CA.